FACEBOOK DAN PERUBAHAN PERILAKU DIKALANGAN REMAJA (STUDI KASUS DI DESA TIGARUNGGU KECAMATAN PURBA KABUPATEN SIMALUNGUN) - Malau, Jens Cinta G; Marnelly, T.Romi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This thesis is submitted in order to qualify holds a bachelor of sociology. With the title" Facebook And Behavioral Changes In Teenagers (Study Case On Teenegers In The Village Purba Tigarunggu The District Simalungun)." The problem is discussed in this paper is how the activity of student / student in the use of social media Facebook and how the influence of Facebook on behavior in the student / student in the use of social media Facebook.Subjects in this study were 7 people. The sampling technique used in this study is the snowball sampling technique. snowball sampling is a sampling technique that initially a small amount, then the sample is given the choice of his friends to be sampled so on so that the number of samples each. The method used is a qualitative research method because this method explain any concerns regarding this title is descriptive. Instrument data filtering is observation, questionnaires and documents. The theory used is the theory and the theory of social change lifestyle. The results were made public, the writer can say that Many students / SMA Negeri 1 Primitive argued facebook is one of the providers layananan more modern communication via internet networking cyberspace. Facebook facilitate communication with others without limits wherever and whenever, either with another person we know and we do not know. Facebook influence young people's behavior in which the onset of the effects of addiction in the use of facebook applications while also use facebook in teenagers SMA Negeri 1 Purba already made in lifestyle and a trend in the youth environment.Keywords: Facebook, Lifestyle, Trend, Teenager